Aerogel fiber composite felt and application thereof
By dispersing hydrogen-absorbing materials in the airgel fiber composite felt, the problem of hydrogen leakage in hydrogen energy vehicles is solved, dual protection of hydrogen energy vehicles is achieved, and safety is improved.
Patent Information
- Application Number
- CN202310903107.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-21
- Publication Date
- 2025-01-21
AI Technical Summary
Existing aerogel fiber composite felts cannot effectively prevent hydrogen leakage in hydrogen energy vehicles, resulting in safety hazards.
By dispersing hydrogen-absorbing materials, such as carbon nanotubes, zeolites or metal-organic framework materials, in the airgel fiber composite mat, a composite material capable of adsorbing and storing hydrogen is formed.
This technology not only provides fire protection and heat insulation effects, but also effectively captures hydrogen leakage, improves the safety of hydrogen energy vehicles and reduces the risk of accidents.
Abstract
Description
Technical Field
[0001] The invention relates to an aerogel fiber composite felt and application thereof, belonging to the technical field of thermal insulation materials. Background Art
[0002] Hydrogen-powered vehicles are vehicles that use hydrogen as energy and rely on the conversion of chemical energy generated by hydrogen reactions into mechanical energy as a driving force. Hydrogen-powered vehicles are divided into two types based on the way hydrogen is used. One is a hydrogen internal combustion engine vehicle: the internal combustion engine burns hydrogen to generate power to propel the vehicle, and the other is a hydrogen fuel cell vehicle: hydrogen or hydrogen-containing substances react with oxygen in the air in a fuel cell to generate electricity to propel the motor, which in turn propels the vehicle. Hydrogen-powered vehicles only produce water vapor during travel, which can effectively reduce the air pollution caused by traditional gasoline vehicles.
[0003] Whether it is a hydrogen internal combustion engine vehicle or a hydrogen fuel cell vehicle that uses hydrogen as a hydrogen source, a hydrogen cylinder for storing hydrogen needs to be installed in the vehicle. However, hydrogen is a flammable gas with an explosion limit of 4.0% to 75.6% (volume concentration), which means that when the volume concentration of hydrogen in the air is between 4.0% and 75.6%, it will explode when it encounters a fire source. If the hydrogen cylinder is not effectively protected when a hydrogen energy vehicle has an accident, it is very easy for hydrogen to escape, causing the vehicle to explode.
[0004] Aerogel is a low-density material with a nano-scale porous structure. Due to its extremely low density and light weight, aerogel is often called solid smoke. At the same time, more than 95% of aerogel is air, so it also has a very excellent thermal insulation effect. For example, the thermal conductivity of silicon aerogel can be as low as 0.013W / m·k at room temperature. Therefore, aerogel is considered to be an outstanding thermal insulation material. However, pure aerogel has poor strength and is difficult to be used as a block material alone for thermal insulation engineering or other fields. The usual solution to the above problem is to combine aerogel with fiber reinforcement materials to form a composite material, namely aerogel fiber felt (aerogel felt), to enhance the strength of the aerogel material. Aerogel fiber felt can be used for hydrogen energy vehicle protection, which can play a good role in fire prevention and heat insulation. However, when the hydrogen in the hydrogen bottle leaks, the existing aerogel fiber felt has a high porosity and the diameter of the pores formed between the fibers is greater than the diameter of the hydrogen molecule. Hydrogen can easily spread through the holes into the interior of the vehicle, thereby failing to play a good protective role and easily causing safety hazards. Summary of the invention
[0005] The purpose of the present invention is to provide an aerogel fiber composite felt capable of absorbing and storing hydrogen.
[0006] The invention also provides an application of an aerogel fiber composite felt.
[0007] In order to achieve the above purpose, the technical solution adopted by the aerogel fiber composite felt of the present invention is:
[0008] An aerogel fiber composite felt comprises an aerogel fiber felt matrix and a hydrogen absorbing material dispersed in the aerogel fiber felt matrix; the main components of the aerogel fiber felt matrix are aerogel fibers and fiber reinforcement materials; the mass ratio of the fiber reinforcement materials to the aerogel fibers is 0-99:1-100.
[0009] The aerogel fiber composite felt of the present invention has hydrogen absorbing materials dispersed in the aerogel fiber felt matrix that can absorb and store hydrogen. When used for protecting hydrogen energy vehicles, it not only has good fireproofing and heat insulation effects, but can also capture hydrogen in the aerogel fiber composite felt that leaks into the power system, thereby achieving dual protection for hydrogen energy vehicles.
[0010] It is understandable that the mass ratio of the fiber reinforcement material to the aerogel fiber in the aerogel fiber felt matrix may be 0:1-100, and in this case, the main component of the aerogel fiber felt is the aerogel fiber.
[0011] Furthermore, the hydrogen absorbing material is one or any combination of carbon nanotubes, zeolites, and metal organic framework materials (MOF). Furthermore, the average particle size of the zeolite is 0.1 to 500 μm, for example, 40 μm, and the specific surface area is 300 to 1000 m 2 / g, for example, 500m 2 / g. The average pore size of the carbon nanotubes is 1-50nm, and the average length is 1-1000μm, for example, the average pore size is 50nm, and the average length is 100μm. The particle size of the metal organic framework material is 70-400nm, and the pore size is 0.34-1.16nm.
[0012] When too much hydrogen absorbing material is used, the fiber felt has low strength, and vibration, collision, etc. may cause the hydrogen absorbing material to fall off. Too little will weaken its ability to capture hydrogen. In order to ensure the strength of the fiber felt and the function of the material, the ratio of the mass of the hydrogen absorbing material to the total mass of the aerogel fiber and the fiber reinforcement material is 12-100:10-120. For example, the mass ratio of the hydrogen absorbing material, the aerogel fiber and the fiber reinforcement material is 12-100:0-20:10-100.
[0013] Furthermore, the average diameter of the aerogel fiber is 10 to 1000 μm, the average porosity is 50 to 99%, and the average pore size is 5 to 50 nm. For example, the average diameter of the aerogel fiber is 20 to 500 μm, the average length is 5 to 100 mm, the average porosity is 50 to 99%, and the average pore size is 5 to 25 nm. The aerogel fiber is prepared by a wet spinning process. Furthermore, the average length of the fiber-reinforced material is 5 to 300 mm, and the average diameter is 1 to 1000 μm, for example, the average diameter is 12 to 1000 μm. The fiber-reinforced material has a porous structure, an average porosity of ≤40%, and an average pore size of 50 to 1000 nm.
[0014] Existing aerogel fibers and fiber reinforcement materials can be used. For example, aerogel fibers are prepared through wet spinning process, aging, solvent exchange, and drying process. Furthermore, the aerogel fiber is preferably one or any combination of silica aerogel fiber, polyimide aerogel fiber, polyamide aerogel fiber, bacterial cellulose aerogel fiber, and graphene oxide aerogel fiber. Furthermore, the fiber reinforcement material is an inorganic fiber reinforcement material and / or an organic fiber reinforcement material. For example, the fiber reinforcement material is an inorganic fiber reinforcement material and an organic fiber reinforcement material, and the mass ratio of the inorganic fiber reinforcement material to the organic fiber reinforcement material is 80~0:19~0.
[0015] The inorganic fiber reinforcement material is preferably ceramic fiber and / or glass fiber. For example, the ceramic fiber is aluminum silicate fiber. The organic fiber reinforcement material is preferably one or any combination of pre-oxidized silk fiber, polyacrylonitrile fiber, polyimide fiber, polyamide fiber, and cellulose fiber.
[0016] Furthermore, the hydrogen absorbing material is fixed in the aerogel fiber felt matrix by a bonding material; the bonding material is fixed by an adhesive. The aerogel fiber composite felt is mainly made of aerogel fibers, fiber reinforcement materials, hydrogen absorbing materials and adhesives.
[0017] Furthermore, the length of the aerogel fiber and the fiber reinforcement material is ≤50 mm, and the aerogel fiber felt is prepared by a method comprising the following steps: providing a mixture of aerogel fiber, fiber reinforcement material, hydrogen absorbing material, adhesive and water; injecting the mixture into a mold for curing, and then drying. For example, the length of the aerogel fiber and the fiber reinforcement material is 2 to 50 mm.
[0018] Furthermore, the lengths of the aerogel fibers and the fiber reinforcement materials are both greater than 50 mm, and the aerogel fiber felt is prepared by a method comprising the following steps: stacking and laying the aerogel fibers and the fiber reinforcement materials and applying an adhesive and a hydrogen absorbing material between every two layers to obtain a cotton blank; then needle-punching the cotton blank, and then curing and drying it;
[0019] Or the aerogel fibers and the fiber reinforcement materials are stacked and laid flat and an adhesive is applied between each two layers to obtain a cotton blank; the cotton blank is then needle-punched, and then cured and dried; the hydrogen absorbing material is sprayed out by the needles during the needle-punching process. For example, the length a of the aerogel fibers and the fiber reinforcement materials satisfies: 50mm<a≤500mm. It is understandable that the stacking and laying of the aerogel fibers and the fiber reinforcement materials can be carried out in a cotton collector.
[0020] Further, the mass ratio of the adhesive to the aerogel fiber is 1-8:97-100. Further, the adhesive is an organic adhesive and / or an inorganic adhesive. The organic adhesive is preferably one or any combination of epoxy resin adhesive, acrylic adhesive, and polyvinyl alcohol adhesive. For example, the acrylic adhesive is an acrylic emulsion. The inorganic adhesive is preferably one or any combination of water glass and cement.
[0021] The technical solution adopted in the application of the aerogel fiber composite felt of the present invention is:
[0022] An application of the above-mentioned aerogel fiber composite felt in the protection of hydrogen energy vehicles.
[0023] When the aerogel fiber composite felt of the present invention is used in the protection of hydrogen energy vehicles, it can not only play the role of fire prevention and heat insulation, but also absorb the hydrogen gas leaked from the hydrogen storage device, thereby improving the safety of hydrogen energy vehicles.
[0024] When the aerogel fiber composite felt of the present invention is used in the protection of hydrogen energy vehicles, the aerogel fiber composite felt is coated with a hydrogen storage device, a hydrogen pipeline, and a valve, so that the release of hydrogen can be slowed down when hydrogen leaks due to vibration or collision, and the hydrogen filling amount in the aerogel fiber composite felt is judged in cooperation with the hydrogen detection system in the vehicle. As the amount of hydrogen increases, the driver receives a warning, and the person has more time to escape from the car. In particular, when a traffic accident occurs, the safety of the person can be better guaranteed. DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with specific implementation methods.
[0026] The aerogel fibers used in the following examples are all prepared through wet spinning, aging, solvent exchange, drying and other processes.
[0027] Example 1
[0028] The aerogel fiber composite felt of the present embodiment comprises an aerogel fiber felt matrix and a hydrogen absorbing material dispersed in the aerogel fiber felt matrix; the main component of the aerogel fiber felt matrix is aerogel fiber; the mass ratio of aerogel fiber to hydrogen absorbing material is 10:100; the aerogel fiber is a silica aerogel fiber with an average length of 10 mm, an average diameter of 20 μm, an average porosity of 99%, and an average pore size of 25 nm; the hydrogen absorbing material is a natural zeolite with an average particle size of 40 μm and a specific surface area of 500 m 2 / g.
[0029] The aerogel fiber composite felt of the present embodiment is prepared by a method comprising the following steps: 100 parts of silica aerogel fibers, 6 parts of water glass, 10 parts of water and 10 parts of zeolite are mixed and stirred evenly, then poured into a mold and placed in a room temperature environment for 30 minutes for preliminary curing, and then placed in an oven for drying and curing to obtain the required aerogel fiber felt.
[0030] Example 2
[0031] The aerogel fiber composite felt of this embodiment includes an aerogel fiber felt matrix and a hydrogen absorbing material dispersed in the aerogel fiber felt matrix; the main components of the aerogel fiber felt matrix are aerogel fibers and fiber reinforcement materials; the mass ratio of aerogel fibers, fiber reinforcement materials and hydrogen absorbing materials is 100:20:12; the aerogel fibers are silica aerogel fibers with an average length of 5 mm, an average diameter of 500 μm, an average porosity of 50%, and an average pore size of 5 nm; the fiber reinforcement material is aluminum silicate fiber with an average length of 5 mm and an average diameter of 12 μm; the hydrogen absorbing material is carbon nanotubes with an average length of 100 μm and an average pore size of 50 nm.
[0032] The aerogel fiber composite felt of the present embodiment is prepared by a method comprising the following steps: 100 parts of silica aerogel fibers, 20 parts of aluminum silicate fibers, 8 parts of water glass, 10 parts of water and 12 parts of carbon nanotubes are mixed and stirred evenly, and then placed in a mold at room temperature for 120 minutes for preliminary curing and then placed in an oven for drying and curing to obtain an aerogel fiber felt.
[0033] Example 3
[0034] The aerogel fiber composite felt of the present embodiment includes an aerogel fiber felt matrix and a hydrogen absorbing material dispersed in the aerogel fiber felt matrix; the main components of the aerogel fiber felt matrix are polyimide aerogel fibers and preoxidized silk fibers; the mass ratio of the polyimide aerogel fibers, the preoxidized silk fibers and the hydrogen absorbing material is 10:20:70; the average length of the polyimide aerogel fibers is 100 mm, the average diameter is 100 μm, the average porosity is 80%, and the average pore size is 20 nm; the average length of the preoxidized silk fibers is 300 mm, the average diameter is 1000 μm, the preoxidized silk fibers have a porous structure, an average porosity of 40%, and an average pore size of 1000 nm; the hydrogen absorbing material is a ZIF-8 metal organic framework material purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd., with a particle size of 70-400 nm, a pore size of 0.34-1.16 nm, and a specific surface area of 559 m 2 / g.
[0035] The aerogel fiber composite felt of the present embodiment is prepared by a method comprising the following steps: polyimide aerogel fibers and pre-oxidized silk fibers are alternately stacked and laid flat on a cotton collector, acrylic emulsion is sprayed between each two adjacent layers to obtain a cotton blank with a thickness of 100 mm, and then the cotton blank is needle-punched and dried to obtain an aerogel needle-punched felt; during the needle-punching process, the hydrogen absorbing material is sprayed out through the micropores on the outer surface of the needle diameter and enters the felt; the ratio of the total mass of the sprayed acrylic emulsion to the mass of the polyimide aerogel fiber is 2:98.
[0036] Example 4
[0037] The application of the aerogel fiber composite felt of this embodiment in the protection of hydrogen energy vehicles is specifically to completely cover the hydrogen storage device, hydrogen pipelines, valves and other places inside the vehicle where there is a risk of hydrogen leakage with the aerogel fiber composite felt of Example 1, 2 or 3. The hydrogen storage device is surrounded by a high-thickness aerogel fiber composite felt, and the hydrogen pipelines and valves are covered with a slightly thinner composite felt, thereby achieving protection for hydrogen energy vehicles.
[0038] Experimental example
[0039] The aerogel composite fiber felts of Examples 1 to 3 were cut The samples were used for testing. Referring to GB / T1038-2000 "Plastic Film and Sheet Gas Permeability Test Method - Pressure Difference Method", the hydrogen permeability of the samples was tested. The test results are shown in Table 1.
[0040] Table 1 Test results
[0041] Transmittance % Example 1 - Sample 70.1 Example 2 - Sample 73.5 Example 3 - Sample 68.4
Claims
1. An aerogel fiber composite felt, characterized in that: The invention comprises an aerogel fiber felt matrix and a hydrogen absorbing material dispersed in the aerogel fiber felt matrix; the main components of the aerogel fiber felt matrix are aerogel fibers and fiber reinforcement materials; the mass ratio of the fiber reinforcement materials to the aerogel fibers is 0-99:1-100.
2. The aerogel fiber composite felt according to claim 1, characterized in that: The hydrogen absorbing material is one or any combination of carbon nanotubes, zeolites, and metal organic framework materials.
3. The aerogel fiber composite felt according to claim 2, characterized in that: The average particle size of the zeolite is 0.1-500 μm; the average pore size of the carbon nanotube is 1-50 nm, and the average length is 1-1000 μm.
4. The aerogel fiber composite felt according to claim 2, characterized in that: The ratio of the mass of the hydrogen absorbing material to the total mass of the aerogel fiber and the fiber-reinforced material is 12-100:10-120.
5. The aerogel fiber composite felt according to any one of claims 1 to 4, characterized in that: The average diameter of the aerogel fiber is 10-1000 μm, the average porosity is 50-99%, and the average pore size is 5-50 nm.
6. The aerogel fiber composite felt according to any one of claims 1 to 4, characterized in that: The aerogel fiber is one or any combination of silica aerogel fiber, polyimide aerogel fiber, polyamide aerogel fiber, bacterial cellulose aerogel fiber, and graphene oxide aerogel fiber.
7. The aerogel fiber composite felt according to any one of claims 1 to 4, characterized in that: The fiber reinforcement material has an average length of 5 to 300 mm and an average diameter of 1 to 1000 μm.
8. The aerogel fiber composite felt according to any one of claims 1 to 4, characterized in that: The fiber reinforcement material is an inorganic fiber reinforcement material and / or an organic fiber reinforcement material.
9. The aerogel fiber composite felt according to claim 8, characterized in that: The inorganic fiber reinforcement material is ceramic fiber and / or glass fiber; the organic fiber reinforcement material is one or any combination of pre-oxidized silk fiber, polyacrylonitrile fiber, polyimide fiber, polyamide fiber and cellulose fiber.
10. The aerogel fiber composite felt according to claim 1, characterized in that: The lengths of the aerogel fibers and the fiber reinforcement material are both ≤50 mm. The aerogel fiber felt is prepared by a method comprising the following steps: providing a mixture of aerogel fibers, fiber reinforcement material, hydrogen absorbing material, adhesive and water; injecting the mixture into a mold for curing, and then drying.
11. The aerogel fiber composite felt according to claim 1, characterized in that: The lengths of the aerogel fibers and the fiber reinforcement materials are both greater than 50 mm, and the aerogel fiber felt is prepared by a method comprising the following steps: stacking the aerogel fibers and the fiber reinforcement materials and applying an adhesive and a hydrogen absorbing material between every two layers to obtain a cotton blank; then needle-punching the cotton blank, and then curing and drying it; Alternatively, the aerogel fibers and fiber reinforcement materials are stacked and laid flat and an adhesive is applied between every two layers to obtain a cotton blank; the cotton blank is then needle-punched, and then cured and dried; during the needle-punching process, the hydrogen absorbing material is sprayed out by the needle.
12. The aerogel fiber composite felt according to claim 10 or 11, characterized in that: The mass ratio of the adhesive to the aerogel fiber is 1-8:97-100.
13. The aerogel fiber composite felt according to claim 10 or 11, characterized in that: The adhesive is an organic adhesive and / or an inorganic adhesive; the organic adhesive is one or any combination of epoxy resin adhesive, acrylic adhesive, and polyvinyl alcohol adhesive; the inorganic adhesive is one or any combination of water glass and cement.
14. Use of the aerogel fiber composite felt as claimed in any one of claims 1 to 13 in the protection of hydrogen energy vehicles.
Citation Information
Patent Citations
Method for preparing aerogel fiber composite material
CN106747540A
Composite fiber reinforced aerogel felt and preparation method thereof
CN111908889A
Aerogel fiber filling material as well as preparation method and application thereof
CN112813584A
Aerogel fiber core material vacuum insulation panel and preparation method and application thereof
CN112856102A
Non-dusting aerogel felt and production method thereof
CN113352709A
Cited By
Light heat insulation fabric and preparation method thereof
CN122013528A